Beban Ijin Total Pesawat (Pta) Dari Nilai PCN (Pavement Classification Number) di Bandara Kualanamu Medan - Ataline Muliasari (WARTA ARDHIA, 2012)
Construction of an airport including Medan International Airport Kualnnamu need to pay attention to the requirements of the runway pavement. A PCN (Pavement Clansificatton Number) published the AIP (Aerodrome Information Publication). Published PCN value is certainly a reference for the Pilot to land in accordance witli permit total load (PTA) aircraft. Related to the above, it is necessary Permit Review Expense Total Aircraft (PTA) aircraft. Related to the above, it is necessary Permit Review Expense Total Aircraft (PTA) From the value of PCN (Pavement Classification Number) In Kualanamu Medan International Airport.From the survey results revealed that the runway Kualanamu Medan International Airport with a load of total permits aircraft (PTA) 1,217,406 lbs or 608,703 kilograms can accommodate Super Jumbo aircraft A-380 which has a Maximum Take Off Weight (MTOW) IS smaller than the total value of the load pemits aircraft (PTA) is 548.000kg (1,208,000 1b). Pembangunan bandara termasuk Bandara Internasional Kualanamu Medan perlu memperhatikan persyaratan perkerasan landasan pacu. Sebuah PCN (Pavement Nomor Klasifikasi) diterbitkan dalam AIP (Aerodrome Information Publication). Nilai PCN diterbitkan sebagai acuan bagi pilot untuk mendarat sesuai dengan beban ijin total pesawat(PTA).Dari hasil penelitian diketahui bahwa landasan pacu Bandara Internasional Kualanamu Medan dengan beban pesawat izin total (PTA) 1.217.406 lbs atau 608.703 kg dapat menampung pesawat Jumbo Super A-380 yang memiliki maksimum yang Take Off Weight (MTOW) lebih kecil dari total nilai pesawat beban ijin(PTA) adalah 548.OOOkg (1.208.OOO lbs).